W pair production at lepton colliders in the Feynman-diagram gauge - Furusato Hiroyuki; Mawatari Kentarou; Suzuki Yutaro; Zheng Ya-Juan (EPJ Web of Conferences)
In ref. [1], we calculated helicity amplitudes for e−e+ → W−W+ in the Feynman-diagram (FD) gauge analytically, and showed that the cross section can be understood by the individual γ, Z and ν amplitudes in the FD gauge. In this report, we discuss each contribution in the angular distributions in detail.